2013
DOI: 10.1016/j.jtbi.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A unified mathematical model to quantify performance impairment for both chronic sleep restriction and total sleep deprivation

Abstract: Performance prediction models based on the classical two-process model of sleep regulation are reasonably effective at predicting alertness and neurocognitive performance during total sleep deprivation (TSD). However, during sleep restriction (partial sleep loss) performance predictions based on such models have been found to be less accurate. Because most modern operational environments are predominantly characterized by chronic sleep restriction (CSR) rather than by episodic TSD, the practical utility of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 19 publications
1
59
0
Order By: Relevance
“…User entries of sleep durations < 8 h per day degrade performance, and sleep durations > 8 h per day improve performance. Consistent with our previously published "fading memory" concept, 6 the more recent the sleep/wake period, the greater its influence on predicted performance.…”
Section: Initial Conditions and Model Assumptionssupporting
confidence: 88%
“…User entries of sleep durations < 8 h per day degrade performance, and sleep durations > 8 h per day improve performance. Consistent with our previously published "fading memory" concept, 6 the more recent the sleep/wake period, the greater its influence on predicted performance.…”
Section: Initial Conditions and Model Assumptionssupporting
confidence: 88%
“…Here, we used the original UMP to obtain P0(t) for the durations of wake and sleep. 2,7 To obtain the caffeine-effect factor gPD(t,c), we used our previously developed PD model of caffeine, which relates the PK of caffeine to the PD effects via the Hill equation.…”
Section: Extension Of the Ump To Account For Caffeine Effectsmentioning
confidence: 99%
“…Accordingly, it is not clear how well this model predicts objective measures pii: sp-00051- 16 http://dx.doi.org/10.5665/sleep.6164 of neurobehavioral performance under more typical operational conditions-characterized by milder sleep loss and repeated caffeine dosing at levels ranging from ~100 mg to ~200 mg. We recently developed the unified model of performance (UMP), a more parsimonious ("caffeine-free") model, and showed that the UMP provides accurate predictions of objective measures of human performance across numerous studies spanning the continuum of sleep loss-from chronic sleep restriction (CSR) to TSD-at a group-average level. 2,7 Separately, we developed a model that considers the neurobehavioral effects of caffeine, and validated it using three TSD studies. 4,5 Here, we combined the original UMP with our caffeine model into a single, unified modeling framework (henceforth termed UMP), and validated its predictions across a wide range of sleep/wake schedules and caffeine doses.…”
Section: Introductionmentioning
confidence: 99%
“…Early efforts included the three process model of alertness/performance (TPM), developed to predict group performance and alertness throughout a day (14). The more recent unified model of performance expands on the TPM and more closely models individual psychomotor performance variance (1518). In order to use the previous models to predict individual cognitive performance using supervised learning techniques, actual cognitive performance data, usually provided by the psychomotor vigilance test (PVT), is required to update the model–parameter estimates (19).…”
Section: Introductionmentioning
confidence: 99%